Tendências tecnológicas para o beneficiamento de minério de ferro - Felix, Beatriz da Rocha (Universidade Federal de São Carlos, 2025)
Among the various mining products, iron ore holds significant importance for the global economy, primarily as the main source of metallic iron used in steel production. This material is essential in sectors such as construction, the automotive industry, machinery manufacturing, and engineering applications. Iron extraction requires substantial investments in equipment and infrastructure, including heavy machinery, trucks, railways, and bulk carriers. Competitiveness in this sector is closely linked to production costs and the quality of the raw material. Currently, dewatering is widely used in the mining industry for ore beneficiation before processing and transportation due to its lower processing costs and efficiency in removing water from high-moisture materials. However, the mechanical wear associated with this process can lead to high maintenance and replacement costs, as well as significant energy consumption and considerable waste generation due to ore dewatering. Therefore, the implementation of new drying technologies becomes necessary not only to strengthen the competitiveness of iron mining but also to promote more sustainable practices within the industry. In this context, this study explores new heavy metal technologies and identifies the most viable equipment and processes for application in iron ore drying, based on a literature review of scientific articles and journals in the field.
Technological trends for iron ore processing
Keywords: Minério de ferro; Novas tecnologias; Iron ore; Drying; Secador rotativo; Technological trends; Moisture; Rotary dryer; Secagem; Umidade; ENGENHARIAS::ENGENHARIA QUIMICA::PROCESSOS INDUSTRIAIS DE ENGENHARIA QUIMICA